Asymmetric information moderation on the effect of institutional ownership on the oversubscription phenomenon of companies listed on the Indonesian stock exchange 2020-2022 - Nusantari, Patih Rahmawati (Trigin Publisher, 2026)
This study examines the effect of institutional ownership on IPO oversubscription in the Indonesian capital market, explicitly addressing the role of asymmetric information both as an explanatory factor and as a potential moderator. Drawing on signaling theory and information asymmetry theory, the study contributes to the IPO literature by empirically testing whether institutional investors serve as credible signals under conditions of uneven information distribution. Using a sample of 96 oversubscribed IPO firms listed on the Indonesia Stock Exchange during 2020–2022, multiple regression and moderated regression analysis are employed. The findings show that institutional ownership and asymmetric information each exert a positive and economically meaningful effect on oversubscription, while asymmetric information does not significantly moderate the institutional ownership–oversubscription relationship. This result fills a gap in the literature where asymmetric information has largely been treated as either a direct determinant or a conceptual argument, rather than a tested moderating mechanism. The findings imply that heightened information frictions may amplify speculative demand rather than dampen investor participation, with important implications for IPO pricing, disclosure quality, and investor protection in emerging markets.